THE USE OF ANIMATED FILM MEDIA CAN IMPROVE LEARNING OUTCOMES OF GRADE IV SDN 1 TANANTOVEA IN ELEMENTARY SOCIAL STUDIES SUBJECTS - Giftiyah Mariatul (Education Journal, 2020)
The purpose of this study was to determine whether using animated film media could improve learning outcomes of grade IV SDN 1 Tanantovea in elementary social studies subjects. The design of this study is classroom action research (CAR). The use of animated film media can improve learning outcomes of grade IV SDN I Tanantovea in elementary social studies subjects. Judging from the results of student learning in the implementation of pre-action, cycle I and cycle II. This is evidenced by the increase in learning outcomes in the implementation of pre-action obtained classical learning completeness 42.30% or only 11 students who completed. while in the first cycle meeting 1 obtained learning completeness 66.6% the number of students who completed 16 and in the first cycle meeting 2 obtained classical learning completeness 76% 19 students, then in the second cycle meeting 1 obtained classical learning completeness 88.46% the number of students who completed 23 people and in the second cycle meeting 2 obtained 96.15% mastery learning the number of students who completed 25 people. With the use of animated film media, students become more active in following the learning process both in doing the assignments given by the teacher, asking questions, responding to a problem and communicating the results of their work..